Hierarchy of truths revisited - E. J. Echeverria (Acta Theologica)
This article explores the ecumenical significance of the notion of hierarchy of truths introduced at the Second Vatican Council. With some assistance from the great Reformed master of dogmatic and ecumenical theology, G.C. Berkouwer, I show how there exists an order of priority or hierarchy among truths resulting from their different relation to the foundation of the Christian faith; how this hierarchy helps us to understand better what unites and divides Christians in matters of doctrine; why this notion is wrongly interpreted as a justification of doctrinal indifference, and the substantive role it may play in ecumenical dialogue when the distinction between truth and its formulations is properly drawn.